Exercise intensity-specific changes to cerebral blood velocity do not modulate a postexercise executive function benefit. (15th October 2021) - Tari, Benjamin; Shirzad, Mustafa; Behboodpour, Nikan; Belfry, Glen R.; Heath, Matthew
Abstract: Executive function is transiently improved (i.e., <60-min) following a single bout of aerobic exercise. A candidate mechanism for this improvement is an exercise-mediated increase in cerebral blood flow (CBF). Further, it has been proposed that an increase in CBF across the continuum of increasing exercise intensities improves the magnitude of a postexercise executive function benefit (i.e., drive theory); however, this proposal has not been empirically tested. Here, participants completed four experimental sessions: a V̇O2peak test to determine cardiorespiratory fitness and estimated lactate threshold (LT), followed by separate 10-min sessions of light- (i.e., 25 W), moderate- (i.e., 80% estimated LT), and heavy-intensity (i.e., 15% of the difference between LT and V̇O2peak ) aerobic exercise. An estimate of CBF during exercise was achieved via transcranial Doppler ultrasound and near-infrared spectroscopy to quantify blood velocity (BV) through the middle cerebral artery and deoxygenated hemoglobin (HHb), respectively. Executive function was assessed before and after each session via the executive-mediated antisaccade task (i.e., saccade mirror-symmetrical to a target). Results demonstrated that BV increased in relation to increasing exercise intensity, whereas HHb decreased by a comparable magnitude independent of intensity. In terms of executive function, null hypothesis and equivalence tests indicated a comparable magnitude postexercise reduction in antisaccade reaction time across exercise intensities. Accordingly, the magnitude of CBF change during exercise does not impact the magnitude of a postexercise executive function benefit. Highlights: A single bout of exercise improves executive function. This benefit may be facilitated by an increase in cerebral blood flow (CBF). Exercise intensity modulated CBF but did not alter the postexercise benefit to executive function. The magnitude of a CBF change does not impact the magnitude of postexercise executive benefit.